Pembuatan Dan Karakterisasi Komposit Hibrid Kayu Plastik Dari Limbah Kayu Kelapa Sawit Dan Serat Tandan Kosong Bermatrik Polipropilena - Tulus Swasono; Yudi Dwianda (Politeknik Kampar, 2019)
The potential for waste of oil palm wood from company plantations and community gardens after passing its productive age is very large, as well as the waste resulting from processing oil palm in the form of empty fruit bunches. The need for natural wood should be reduced by using wood substitute materials, one of which is wood plastic composite, which uses plastic as a matrix and wood as reinforcement. In order to obtain a hybrid composite with reinforces in the form of palm sawdust and empty bunch fiber as well as a polypropylene matrix with mechanical and physical properties that meet the standard criteria, composite manufacture and characterization were carried out.